Controlling the Properties of Solvent-free Fe3O4 Nanofluids by Corona Structure - Tan, Yumo; Zheng, Yaping; Wang, Nan; Zhang, Aibo (Nano-Micro Letters, 2012)
We studied the relationship between corona structure and properties of solvent-free Fe3O4 nanofluids. We proposed a series of corona structures with different branched chains and synthesize different solvent-free nanofluids in order to show the effect of corona structure on the phase behavior, dispersion, as well as rheology properties. Results demonstrate novel liquid-like behaviors without solvent at room temperature. Fe3O4 magnetic nanoparticles content is bigger than 8% and its size is about 2∼3 nm. For the solvent-free nanofluids, the long chain corona has the internal plasticization, which can decrease the loss modulus of system, while the short chain of corona results in the high viscosity of nanofluids. Long alkyl chains of modifiers lead to lower viscosity and better flowability of nanofluids. The rheology and viscosity of the nanofluids are correlated to the microscopic structure of the corona, which provide an in-depth insight into the preparing nanofluids with promising applications based on their tunable and controllable physical properties.